A Small Molecule Inhibitor of Pex3–Pex19 Interaction Disrupts Glycosome Biogenesis and Causes Lethality in Trypanosoma brucei - Banerjee, Hiren; LaPointe, Paul; Eitzen, Gary; Rachubinski, Richard A. (Frontiers in Cell and Developmental Biology, 2021)
Trypanosomatid parasites, including Trypanosoma and Leishmania, are infectious zoonotic agents for a number of severe diseases such as African sleeping sickness and American trypanosomiasis (Chagas disease) that affect millions of people, mostly in the emergent world. The glycosome is a specialized member of the peroxisome family of organelles found in trypanosomatids. These organelles compartmentalize essential enzymes of the glycolytic pathway, making them a prime target for drugs that can kill these organisms by interfering with either their biochemical functions or their formation. Glycosome biogenesis, like peroxisome biogenesis, is controlled by a group of proteins called peroxins (Pex). Pex3 is an early acting peroxin that docks Pex19, the receptor for peroxisomal membrane proteins, to initiate biogenesis of peroxisomes from the endoplasmic reticulum. Identification of Pex3 as the essential master regulator of glycosome biogenesis has implications in developing small molecule inhibitors that can impede Pex3–Pex19 interaction. Low amino acid sequence conservation between trypanosomatid Pex3 and human Pex3 (HsPex3) would aid in the identification of small molecule inhibitors that selectively interfere with the trypanosomatid Pex3–Pex19 interaction. We tested a library of pharmacologically active compounds in a modified yeast two-hybrid assay and identified a compound that preferentially inhibited the interaction of Trypanosoma brucei Pex3 and Pex19 versus HsPex3 and Pex19. Addition of this compound to either the insect or bloodstream form of T. brucei disrupted glycosome biogenesis, leading to mislocalization of glycosomal enzymes to the cytosol and lethality for the parasite. Our results show that preferential disruption of trypanosomal Pex3 function by small molecule inhibitors could help in the accelerated development of drugs for the treatment of trypanosomiases.